Policy Debate | International Responses to Global Epidemics: Ebola and Beyond - Monica Rull; Ilona Kickbusch; Helen Lauer (Revue Internationale de Politique de Développement)
Editor’s Note: These papers are contributions to the ‘Policy Debate’ section of International Development Policy. In this section, academics, policy-makers and practitioners engage in a dialogue on global development challenges. Papers are copy-edited but not peer-reviewed. Instead, the initial thematic contribution is followed by critical comments and reactions from scholars and/or policy-makers or practitioners. This debate can be pursued on the Journal’s blog (http://devpol.hypotheses.org/956) where you are invited to share your reflections under your name.The initial paper was written by Monica Rull, from Doctors Without Borders (Médécins sans Frontières) Switzerland. Monica Rull provides an in-depth and lucid examination of the collective failure to respond in a timely and efficient manner to global epidemics. Starting from the recent Ebola crisis in West Africa, the piece pinpoints a number of weaknesses in the international system in terms of the identification of, and response to, global epidemics and suggests ways to improve it.The initial paper is followed by critical comments of two authors: Ilona Kickbusch, Director of the Global Health Programme and Adjunct Professor at the Graduate Institute of International and Development Studies, Geneva and Helen Lauer, Professor at the Department of Philosophy and Religious Studies, College of Humanities, University of Dar es Salaam.